Value of contracting as an active purchasing mechanism of healthcare services : a South African case study - Pillay, Ravi (Health Economics Unit, 2015)
Strategic purchasing is a way of ensuring that the healthcare interventions that are provided, improves the health systems responsiveness. Contracting for health services, as a component of strategic purchasing, has been promoted as an important mechanism to improve the efficiency of resource use, quality in health care service provision and increase accountability, all of which contribute towards improving health system performance. Over the past two decades, many countries have adopted contracting as a mechanism to positively impact the performance of the health system. However, despite the increasing interest and experimentation with contracting as a way to improve health systems, the results remain controversial. Within South Africa's private healthcare market, medical schemes represent the largest source of private healthcare funding. Given the rate of increase of medical inflation within the South African private healthcare market, there is an absolute need for medical schemes to become more strategic in their purchasing decisions. This dissertation aims to address the gaps identified in the contracting literature by providing empirical evidence from an evaluation of a contractual agreement between a healthcare financing agency, medical scheme, and a managed care organisation in the private health sector in South Africa for the provision of a back rehabilitation programme to reduce the cost of back surgeries. The dissertation also attempts to formulate key learnings that will inform future policies regarding contracting for healthcare services within the private and public health sector in South Africa.